(untitled) (Terr@ Plural, 2019)
This paper aimed to optimize the method of obtaining the intrinsic vulnerability index of the aquifers to the pollution (IVIAP) conferring to the variable infiltration and recharge the matrix combination between the slope intervals and the relative density of vegetation cover. In addition to the collection of hydrolytic data from the aquifer units, the Geographic Information System (GIS) was used to map 34 springs in Rondonópolis, MT, compile data from the groundwater table of tubular wells, and correct satellite and radar images from medium-high spatial resolutions. The IVIAP was identified as an alternative, simple and effective method to qualify vulnerabilities to aquifer pollution, especially in regions where there is a shortage of hydrological information.